Memorizing the Quran to Improve Student Learning Achievement - Henrik, Gomez Per; Anil, Valo; Maria, Delic (World Psychology, 2023)
The Qur'an is the holy book for all Muslims around the world. This study found a problem about students' difficulties in memorizing Qur'anic verses. Memorizing is not an easy task, there are times when we have difficulty in memorizing causing our memorization to stagnate. This study aims to not only add insight or thought to the reader, but also aims to find what allows students to have difficulty memorizing the holy verses of the Qur'an, or what are the obstacles for students in memorizing the Qur'an verses. With many students memorizing the Qur'an, it will create a generation that is moral and noble. This research uses the observation method, where this method can see directly the environmental conditions concerned or with the people involved. This method will get research results that satisfy researchers in conducting a study. This research will find out how to run the Quranic memorization program and what are the obstacles for someone in memorizing Quranic verses. And find out what are the problems faced by the memorizers of al-quraan. Memorizing the Qur'an has an important role in life. A worship expert has difficulty when memorizing al-quraan, therefore make memorizing al-quraan as our daily habit in order to get the grace of allah swt